KI als neue didaktische Partnerin? Einstellungen von DaF-Lehramtsstudierenden zum Einsatz von KI im Studium und im DaF-Unterricht - Retelj, Andreja (70 Jahre Germanistik in Zadar: Rückblicke, Einblicke, Ausblicke, 2026)
This paper examines how prospective teachers of German as a foreign language are already using artificial intelligence (AI) during their studies and what functions they attribute to this technology for their future teaching practice. Since little is currently known about teacher trainees’ attitudes toward the use of AI tools, a questionnaire was used to gather data on their personal usage patterns and potential application scenarios in German as a foreign language classroom. The results show that AI has already become an everyday tool for many future teachers of German as a foreign language. They primarily use AI tools for writing and editing texts, structuring complex tasks, and creating learning materials during their practicum phase. Furthermore, the findings reveal that the majority of respondents view the use of AI in future German as a foreign language teaching positively and perceive the technology more as an opportunity than a threat.